DOP35 Increasing incidence of pouchitis among patients undergoing ileal pouch-anal anastomosis between 1996 and 2018: A population-based Danish cohort study. (21st January 2022) - Barnes, E; Allin, K; Iversen, A; Herfarth, H; Jess, T
Abstract: Background: Current knowledge regarding the epidemiology of pouchitis is based on highly selected, mostly single-center, patient cohorts. Our objective was to prospectively determine the population-based incidence of pouchitis in patients with ulcerative colitis (UC) in the first 2 years after ileal pouch-anal anastomosis (IPAA) and analyze time trends of the incidence of pouchitis. Methods: We used national registries to establish a population-based cohort of all Danish patients undergoing proctocolectomy with IPAA UC between 1996 and 2018. The primary outcome was the development of pouchitis within the first 2 years after IPAA, evaluated by time period of IPAA. The period of IPAA was categorized as follows: 1996–2000 (pre-biologic-1), 2001–2005 (pre-biologic-2), 2006–2010 (early-anti-TNF), 2011–2014 (expanding anti-TNF), 2015–2018 (current biologic). Pouchitis was defined using a previously developed case-finding definition for use in administrative claims data. Kaplan Meier and Cox Proportional Hazard modeling were utilized in the evaluation of time to development of pouchitis. Results: We identified 1, 664 patients that underwent an IPAA for UC. The cumulative incidence of pouchitis in the 2 years after IPAA increased throughout the study period, from 40% in 1996–2000, (95% CI:35%-46%) to 55% in 2015–2018, (95% CI:48%-63%, Table 1). Patients undergoing surgery between 2015–2018 also demonstrated an increased risk of pouchitis compared to the earliest study period (1996–2000) after adjusting for sex, age, and socioeconomic status (Hazard Ratio [HR] 1.57, 95% CI:1.20–2.05, Table 2, Figure 1). In a separate model adjusting for the same clinical and demographic factors, there was no significant relationship between the preoperative use of anti-tumor necrosis factor alpha therapy use and the risk of pouchitis when evaluated in the entire population (HR 1.14, 95% CI:0.93–1.40) and when evaluated by time period of surgery. Conclusion: This first population-based study demonstrated a 15% absolute and 38% relative increase in the incidence of pouchitis among patients undergoing surgery between 1996 and 2018, with the greatest cumulative incidence of pouchitis demonstrated in the most recent era (2015–2018). The striking increase in the incidence of pouchitis highlights the need for further research into causes and prevention of pouchitis.